Empowering MSME Through Socialization and Training in Producing Simple Financial Reports in Tourism Villages - Ghofar, Abdul; Khoirul Umam Hasbiy; Wuri Cahya Handaru; Mirna Amirya; Areta Widya Kusumadewi; Wahyu Kartika Larasti; Jawo, Mohammed (The International Journal of Accounting and Business Society, 2023)
Aim - The aim of exists article This are (1) Increase MSME skills and understanding of making report finance simple For help they manage business they with more efficient (2) Encouraging MSMEs to operate practice more business _ transparent with provide report more finances _ accurate (3) Helping MSMEs in Tourism Villages Attack to own more access _ Good to source Power finance , like loans and support from the bank or institution finance other , with own report more finances _ good .Method - This article use method qualitative with approach studies case , so the result nature analytical and descriptive . Population from study This is a tourist village throughout Indonesia and is becoming sample study This is a Tourist Village Attack in the District Blitar , East Java.Findings - Moderate obstacles faced by MSME actors in Tourism Villages attack that is majority MSME actors not yet do recording on transaction required income and expenses _ in the production process so that understanding about importance making report finance still very lacking .Implications Practical - This article help MSME actors in understand importance make report finance simple as tool For monitor performance business from time to time as well as increase quality of MSMEs in Tourism Villages Attack , as form contribution to growth economy local which can also be done practiced by all perpetrator business in Indonesia.Originality - This article explained problems faced by MSMEs especially _ _ about literacy finance so that Can give example Not yet optimally understanding importance make report finance simple can reduce supposed profits _ Can maximized .